The problem of HIV infections and AIDS in the world in relation to WHO activities - Zuzanna Chilimoniuk; Aleksandra Borkowska; Anna Sobstyl; Aleksandra Chałupnik; Maciej Dobosz; Paweł Stanicki; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2019)
The Problem of HIV infections and AIDS has been known for years. Effective prevention and treatment is a challenge of modern medicine. Studies conducted by the WHO show that Africa, in terms of morbidity and deaths, is the first among the regions included in this study. Nowadays, diagnosis of HIV infections is highly developed. This allows for quick and easy testing to confirm the infection, even in pregnant women. Across the globe, 59% of people infected with HIV receive antiretroviral treatment that allows them to function normally in society. Early and appropriate use of antiretroviral drugs significantly reduces the transmission of infection to other people and reduces the risk of having a child with HIV. Awareness of this infection among the general public and especially among young people is limited, which is why social campaigns play an important role in prevention.